2021
DOI: 10.3389/fonc.2021.769665
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Biomarkers Originating From the Tumor Stroma of Betel Quid-Associated Oral Cancer Tissues

Abstract: BackgroundPartial epithelial-mesenchymal transition (p-EMT) is a distinct clinicopathological feature prevalent in oral cavity tumors of The Cancer Genome Atlas. Located at the invasion front, p-EMT cells require additional support from the tumor stroma for collective cell migration, including track clearing, extracellular matrix remodeling and immune evasion. The pathological roles of otherwise nonmalignant cancer-associated fibroblasts (CAFs) in cancer progression are emerging.MethodsGene set enrichment anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Examination of miRNAs in plasma samples from tumors and controls demonstrated an up‐regulation of various miRNAs, including miR‐24, miR‐181, miR‐196a, miR‐10b, miR‐187*, in OSCC tissues and plasma compared to control samples. 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 Additionally, elevated expression of miR‐155 was observed in tissue and plasma samples of LSCC compared to controls. 86 , 87 Conversely, reduced expression of miR‐497 was noted in tissue and plasma of nasopharyngeal carcinoma (NPC) patients relative to noncancerous control patients' plasma.…”
Section: Diagnosis In Personalized Medicinementioning
confidence: 95%
See 1 more Smart Citation
“…Examination of miRNAs in plasma samples from tumors and controls demonstrated an up‐regulation of various miRNAs, including miR‐24, miR‐181, miR‐196a, miR‐10b, miR‐187*, in OSCC tissues and plasma compared to control samples. 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 Additionally, elevated expression of miR‐155 was observed in tissue and plasma samples of LSCC compared to controls. 86 , 87 Conversely, reduced expression of miR‐497 was noted in tissue and plasma of nasopharyngeal carcinoma (NPC) patients relative to noncancerous control patients' plasma.…”
Section: Diagnosis In Personalized Medicinementioning
confidence: 95%
“…Examination of miRNAs in plasma samples from tumors and controls demonstrated an up‐regulation of various miRNAs, including miR‐24, miR‐181, miR‐196a, miR‐10b, miR‐187*, in OSCC tissues and plasma compared to control samples 77–85 . Additionally, elevated expression of miR‐155 was observed in tissue and plasma samples of LSCC compared to controls 86,87 .…”
Section: Diagnosis In Personalized Medicinementioning
confidence: 98%
“…In the same vein, Liu et al used seven existing RNA expression datasets from a broad spectrum of cancers to define CAF populations. From their analysis, three main fibroblast populations crystalized, i.e., CAF1/myCAF (markers PDPN, FN1), CAF2/iCAF, and myofibroblasts [ 37 ]. Taken together, these data suggest that there could be an overemphasis on ACTA2-positive “CAFs,” and one can boil down CAFs to two main subtypes which do not exist in PMDs.…”
Section: Activated Fibroblasts and Myofibroblastsmentioning
confidence: 99%
“…In our experiments, p-EMT but not mesenchymal cells exhibited multicellular cohesiveness and spheroid invasion in vitro, as well as collective angiolymphatic and perineural invasions in an immunodeficient mouse model [ 40 ]. Integrated transcriptomic analysis of xenograft tissues revealed that p-EMT and mesenchymal cells coexisted with different subtypes of host cancer-associated fibroblasts (CAFs): inflammatory and myofibroblastic CAFs, respectively [ 41 , 42 ]. Thus, our data support the hypothesis that tumor and stromal cells might influence each other through epigenetically driven cellular plasticity and coevolve to form an ecosystem [ 37 ].…”
Section: Epigenetic Alterations Phenotypic Plasticity and Malignant T...mentioning
confidence: 99%